1996
DOI: 10.1080/08838159609364369
|View full text |Cite
|
Sign up to set email alerts
|

Negative video as structure: Emotion, attention, capacity, and memory

Abstract: This paper uses a limited capacity information processing theory of television viewing to investigate the effects of graphic negative video at four levels of processing (attention, capacity, encoding, and retrieval) and on two dimensions of emotional experience (arousal and valence). Results indicate that the presence of negative video in news stories increases attention, increases the amount of capacity required to process the message, increases the ability to retrieve the story, facilitates recognition of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
208
1
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(233 citation statements)
references
References 23 publications
14
208
1
7
Order By: Relevance
“…For example, Bushman (1998) found that angry affect served as a mediator between the relationship of viewing a violent TV program and decreased commercial memory. In addition, research suggests that viewing a violent news story generates arousal and negative emotions (Lang et al, 1996). Arousal and negative emotions could prompt retrospective disruption for commercials embedded in the programs (Newhagen, 1998).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…For example, Bushman (1998) found that angry affect served as a mediator between the relationship of viewing a violent TV program and decreased commercial memory. In addition, research suggests that viewing a violent news story generates arousal and negative emotions (Lang et al, 1996). Arousal and negative emotions could prompt retrospective disruption for commercials embedded in the programs (Newhagen, 1998).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…One possible explanation for this result is that post-learning stress enhances word memory performance, but relies on material arousal and not on the valence of stimuli. Both the valence and arousal of the material mediate the processing of emotional memory (Lang, Newhagen, & Reeves, 1996), and arousal ranges from calming to exciting, while valence ranges from positive to negative. In examining the relationship between the effect of acute stress on emotional memory, especially pre-learning stress and acute stress on memory retrieval, Wolf (2009) asserted that arousal might be more important than valence with regard to the occurrence of stress effects.…”
Section: Discussionmentioning
confidence: 99%
“…(This is akin to motivational activation. [55,56]) Witnesses who are more nonverbally expressive in hearings may be making greater effort to persuade the committee members (as studies of the use of gestures have shown [52]), or certain facial expressions may be expressing latent emotions.…”
Section: Coding Of Nonverbal Behaviour In Parliamentary Hearingsmentioning
confidence: 99%
“…To be sure, measures for coding should avoid incurring inconsistencies arising from human idiosyncrasies, [53] and to the extent that the agreed results reported below are based upon a simple 100% agreement that one set of witnesses or committee exhibited relatively more nonverbal cues (anger, happiness, etc) than the other set of witnesses or committee, the bulk of the coding results do not report as findings any inconsistencies among the coders (and so, a measure such as Krippendorff's Alpha is not used). Studies do not usually discuss differences among coders (although exceptions include: Schubert and colleagues, who comment on a coder's "idiosyncratic tendency to overcode"; [43] and Bucy and Gong, who discuss specific techniques for improving intercoder reliability and precision [9,[55][56][57][58]) and yet-as discussed earlier-receivers of nonverbal messages do not necessarily respond in similar ways, as these signals are conditional on pre-existing attitudes and the situational context of the behaviour, and some individuals are simply more adept than others in discerning the meaning of the signals. Finally, "stereotypical" university undergraduates have been criticized for being "socially compliant" and "more likely to be mercurial in their attitudes because of lack of self-knowledge."…”
Section: Coding Of Nonverbal Behaviour In Parliamentary Hearingsmentioning
confidence: 99%